POLA PENDIDIKAN PADA KELUARGA JAMAAH TABLIGH DI KALIMANTAN SELATAN - Ahmad Dzaky (Jurnal Studi Islam Lintas Negara (Journal of Cross-Border Islamic Studies), 2020)
EDUCATION PATTERNS IN THE TABLIGHI JAMAAT FAMILIY IN SOUTH KALIMANTAN. Early education in the family is a solid foundation for the next generation in treading the increasingly complex problems of life. Various family problems in the modern era have become the basis for uncontrolled children's education. In the deepness of the problems facing modern society, there is a group of people who actually carry out anti-mainstream activities. Not doing activities for the sake of hedonistic things, on the contrary, willing to sacrifice energy, thoughts, property, even life for the sake of Islam through peaceful preaching. This indicates that they have tasted the sweetness of faith in their own way, this movement is called Tablighi Jamaat. The main problem is what is the pattern of education in Tablighi Jamaat families? The approach used in this research is qualitative and the type of research used is phenomenology. The findings: the pattern of education in the Tablighi Jamaat family is authoritarian and democratic. Authoritarian means members of the Tablighi Jamaat direct their children to follow in the footsteps of the da'wah they live, this is done to introduce and instill the spirit of da'wah in children. After the child grows up, a democratic pattern occurs, namely a two-way dialogue between parents and children about the educational institution they will choose. Parents give freedom in this case, but the values ​​and spirit of preaching must be maintained by providing time to be active in the activities of preaching the Tablighi Jamaat. These two things are synonymous with transmission and transaction patterns.